O Serogroup-Specific Touchdown-Multiplex Polymerase Chain Reaction for Detection and Identification of Vibrio cholerae O1, O139, and Non-O1/Non-O139 - Adisak Bhumiratana; Achiraya Siriphap; Nutsarin Khamsuwan; Jednipit Borthong; Kaknokrat Chonsin; Orasa Sutheinkul (Biochemistry Research International)
A novel, sensitive locus-specific touchdown-multiplex polymerase chain reaction (TMPCR), which is based on two-stage amplification pertaining to multiplex PCR and conditional touchdown strategy, was used in detecting and differentiating Vibrio cholerae serogroups. A panel of molecular marker-based TMPCR method generates reproducible profiles of V. cholerae-specific (588 bp) amplicons derived from ompW gene encoding the outer membrane protein and serogroup-specific amplicons, 364 bp for the O1 and 256 bp for the O139, authentically copied from rfb genes responsible for the lipopolysaccharide biosynthesis. The TMPCR amplification efficiency yields either equally or unequally detectable duplex DNA bands of the O1 (588 and 364 bp) and O139 (588 and 256 bp) or a DNA fragment of non-O1/non-O139 (588 bp) while providing no false positive identifications using the genomic DNA templates of the other vibrios and Enterobacteriaceae. The reciprocal analysis of two-template combinations demonstrated that, using V. cholerae O1, O139, or equally mixed O1 and O139, the TMPCR had a detection limit of as low as 100 pg of the O1, O139, or non-O1/non-O139 in reactions containing unequally or equally mixed gDNAs. In addition, the O serogroup-specific TMPCR method had 100% agreement with the serotyping method when examined for the serotyped V. cholerae reference strains and those recovered from clinical samples. The potential benefit of using this TMPCR tool would augment the serotyping method used in epidemiological surveillance and monitoring of V. cholerae serogroups, O1, O139, and non-O1/non-O139 present in clinical and environmental samples.